In silico design of a novel chimeric shigella IpaB fused to C terminal of clostridium perfringens enterotoxin as a vaccine candidate. Issue 1 (1st January 2018) - Arabshahi, Sina; Nayeri Fasaei, Bahar; Derakhshandeh, Abdollah; Novinrooz, Aytak
ABSTRACT: This study aimed to design a novel chimeric protein in silico to serve as a serotype-independent vaccine candidate against Shigella . The chimera contains amino acid residues 240–460 of Shigella invasion plasmid antigen B (IpaB) and the C-terminus of Clostridium perfringens enterotoxin (C-CPE). Amino acid sequences of 537 peptide linkers were obtained from two protein linker databases. 3D structures of IpaB-CPE290–319, IpaB-CPE184–319, IpaB-CPE194–319 and 537 newly designed IpaB-linker-CPE290–319 constructs with varying linker regions were predicted. These predicted 3D structures were merged with the 3D structures of native IpaB240–460, CPE194–319, CPE184–319 and CPE290–319 to select the structure most similar to native IpaB and C-CPE. Several in silico tools were used to determine the suitability of the selected IpaB-C-CPE structure as a vaccine candidate. None of the 537 linkers was capable of preserving the native structure of CPE290–319 within the IpaB-linker-CPE290–319 structure. In silico analysis determined that the IpaB-CPE194–319 3D structure was the most similar to the 3D structure of the respective native CPE domain and that it was a stable chimeric protein exposing multiple B-cell epitopes. IpaB-CPE194–319 was designed for its capability to bind to human intestinal epithelial and M cells and to accumulate on these cells. The predicted B-cell epitopes are likely to be capable of inducing a mucosal antibody response in the human intestine against Shigella IpaB. This study also showed that the higher binding affinities of CPE184–319 and CPE194–319 to claudin molecules than those of CPE290–319 is the result of preserving the 3D structures of CPE184–319 and CPE194–319 when they are linked to the C-termini of other proteins.